Incorporation of MnO2 into boron-enriched electrospun carbon nanofiber for electrochemical supercapacitors - Yang, Cheol-Min; Kim, Bo-Hye (ELSEVIER SCIENCE SA, 2019)
MnO2- and boron-incorporated polyacrylonitrile (PAN)/pitch-based carbon nanofiber (PPBMn) composites for electrochemical supercapacitors are successfully fabricated by one-step electrospinning using a combined solution of MnCl2, B2O3, PAN, and pitch. The surface morphologies, microstructures, surface chemical states, and texture properties of the PPBMn composites are investigated and the effect of the MnCl2 content on the electrochemical performance in aqueous electrolytes is also examined. The PPBMn composites exhibit a high specific surface area with mesoporous structure, and boron and MnO2 functional groups as electroactive sites. Enriched boron and MnO2 functional groups provide low internal resistance of charge diffusion by better wettability of electrolyte ions into the pores and also accommodate more charges, leading to high gravimetric capacitance and energy density, and enhanced cycling stability. Therefore, the PPBMn series exhibits superior electrochemical performance through the combined functions of their double-layer capacitance and pseudo-capacitive character through the high porosity, higher attractive force by the surface chemical activity and the wettability between the electrode and electrolyte. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: ACTIVATED CARBON; MESOPOROUS CARBON; PERFORMANCE; GRAPHENE; CAPACITANCE; NANOPARTICLES; COMPOSITES; NANOTUBES; GRAPHITE; WEBS